Demand, Supply Response and Preference Switch for Rice in Nigeria (2014)
The phenomenon of increasing rice importation defying several policy interventions has been of great concern in Nigeria. This rising importation is however driven by increasing demand, shortage in domestic supply and consumers’ preference for imported rice. Yet, comprehensive national studies on determinants of demand, supply response and preference switch for rice are scarce. Thus, the determinants of demand, supply response and preference switch for rice were investigated. Secondary data from the Nigeria Living Standard Survey (NLSS) of 2004 conducted by the National Bureau of Statistics (NBS) and time series data from the official records of International Rice Research Institute (IRRI), 1960-2008 were used. Due to elimination of households with missing values on variables of interest, a total of 18,861 out of 21,900 households were used in the NLSS. Variables used in NLSS included Household Size (HS), Non-Food Total Expenditure (NFTE), Years of Education (YE), sector (urban/rural), occupation (farming/non-farming) and Membership of Association (MA) which were hypothesized to influence household expenditures on Imported Rice (IR), Improved Domestic Rice (IDR) and Local Rice (LR). Data on area cultivated, level of import, fertilizer consumption and prices were used in IRRI rice statistics and these variables were also hypothesized to influence supply (output) of rice. Data were analysed using descriptive statistics, Tobit regression model, vector error correction model and generalised least square regression at p= 0.05. The HS and YE were 4.9±2.9 and 6.8±6.3 years, respectively. Rural dwellers, farmers and members of association constituted 76.1%, 82.7% and 54.2%, respectively. Monthly rice expenditure was N2, 712.40, representing 25.0% of total monthly food expenditure. The expenditure share of IR (45.0%) was higher than IDR (30.0%) and LR (25.0%). Urban sector, YE, HS and NFTE increased the demand for IR by 4.0×10-03, 2.0×10-04, 1.0×10-03 and 1.0×10-09, respectively, while Farming Occupation (FO) reduced it by 9.0×10-03. Also, FO increased IDR demand by 8.0×10-03. Conversely, HS, NFTE, and MA reduced IDR demand by 9.0×10-04, 2.0×10-08 and 1.0×10-09, respectively. Also, NFTE and MA, respectively, increased LR demand by 6.0×10-09 and 4.0×10-03. Price elasticities of IR, IDR and LR which were -3.0×10-03, -7.0×10-04 and -2.0×10-03, respectively implied that rice was price inelastic. Also, income elasticities of IR, IDR and LR which were, respectively, 7.0×10-08, 2.0×10-07 and 1.0×10-07 classified rice as ‘necessities’ and ‘normal’ good. In the long-run, area cultivated and fertilizer consumption increased rice output by 2.8 and 2.3 respectively. Rural Sector (RS), HS, FO, and price of IR increased consumers’ switch from IR to IDR by 55.1, 6.6, 130.4, and 30.7, respectively, while price of IDR reduced it by 19.4. Price of IR and RS positively influenced switch from IR to LR by 2.0 and 70.2, respectively, while price of LR reduced it by 16.3. Education and urban livelihood increased demand for imported rice. Increasing rice area cultivated and usage of fertilizer may boost domestic rice supply. Price reduction will be a veritable tool in switching consumers’ preference from imported to improved domestic and local rice.